2005
DOI: 10.1021/la0500326
|View full text |Cite
|
Sign up to set email alerts
|

Thermodesorption Studies of Energetic Properties of Ni/MgO−Al2O3 Catalysts. Determination of Adsorption Energy Distribution Functions

Abstract: The thermodesorption spectra of hydrogen from coprecipitated catalysts (70-x)NiO-xMgO-30Al(2)O(3) (x = 0-50%(wt)) are reported. The catalysts were calcined at 400 degrees C and reduced with H(2) at 20-800 degrees C and for 3 h at 800 degrees C. NiO reduction degree was between 49.3 and 92.1%. The active surface areas changed from 8.4 to 32.4 m(2)/g whereas mean size of nickel crystallites was between 3.7 and 9.7 nm. The TPD spectra were next analyzed in order to determine the adsorption energy distributions fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 30 publications
(58 reference statements)
0
30
0
Order By: Relevance
“…[7][8][9][10] The above considerations lead to the conclusion that in most of the experimental situations it is sufficient to take for analysis only simplified versions of the SRT kinetic equation, i.e. The gas phase in such an experiment is always pumped off and the number of molecules in the gas phase is kept low.…”
Section: Fundamental Features Of the Statistical Rate Theory Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] The above considerations lead to the conclusion that in most of the experimental situations it is sufficient to take for analysis only simplified versions of the SRT kinetic equation, i.e. The gas phase in such an experiment is always pumped off and the number of molecules in the gas phase is kept low.…”
Section: Fundamental Features Of the Statistical Rate Theory Approachmentioning
confidence: 99%
“…Set (24) describes the case of isothermal desorption, however, more typical is the thermodesorption process, i.e. 10 Eqn (24) can be expressed in terms of dimensionless quantities using the set of substitutions (14)(15)(16)(17). In such a case set (24) is still valid, however, one has to remember that the temperature is then a certain function of time, usually dT/dt = b where b is the heating rate.…”
Section: Pressure Dependence Of Desorption Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The TPD-H 2 profiles of catalysts with the variable MgO/NiO ratios were subjected to a quantitative analysis in ref. [42]. The determined adsorption energy distribution functions showed that the catalysts containing ≤ 27.3 wt.% of MgO revealed qualitatively similar bands of the adsorption energy.…”
Section: Disscusionmentioning
confidence: 82%
“…However, the increasing amount of MgO alters the population of various types of adsorption centers found on catalysts active phases. Thus, the amount of MgO modifies significantly the morphology of nickel crystallites formed during the reduction process [42].…”
Section: Disscusionmentioning
confidence: 99%